A distributed-parameter control system using electromagnetic neural stimulation for human–machine perception interface. Issue 1 (2nd January 2022) - Li, Min
ABSTRACT: This article presents a new design of a distributed-parameter control system for human–machine perception interface, which is capable of precisely stimulating the neural systems with electromagnetic fields. By discretising the neural systems, a state-space representation of the electromagnetic stimulation is developed to facilitate the following design and analysis. A forward controller with multiple inputs and multiple outputs is consequently designed to estimate the excitation current. This novel approach enables the applications of the well-established control theory to analyse the system. The feasibility and accuracy of the control system are numerically illustrated and validated with the applications of Transcranial Magnetic Stimulation (TMS) and retinal stimulation. The results indicate that the newly designed control system can not only generate electromagnetic stimulation with better attenuation and focality than the most widely used Figure-8 coil, but also transmit the patterns extracted from images with electromagnetic stimulations to human retinas.